Further documents from F. Taylor Ostrander - Samuels, Warren J., 1933- (Emerald, 2006)
This volume continues publication of the class notes of F. Taylor Ostrander at Williams College, 1929-32. The courses are Principles of Economics, Money and Banking, Public Finance, the Senior Seminar and Review of Political Theory. Also included are two memoranda on Franklin D. Roosevelt, from 1933 and 1945, and a memoir on the founding of the Williams College Liberal Club. This book provides a look into the thinking of leading economists in the 20th century. F. Taylor Ostrander is a very influential economist and the insight gained by his classnotes is extremely valuable.
Keywords: Economics -- Study and teaching (Higher); Economics -- Methodology.; Economics -- Research.; elektronické knihy; electronic books